Efektivitas Pemberian Air Rebusan Daun Salam untuk Mengatasi Ketidakstabilan Kadar Glukosa Darah : Hiperglikemia pada Diabetes Mellitus Tipe II di Wilayah Binaan Puskesmas Kedu - Khasanah, Nurul; Parmilah; Lusmiati Anisah, Retno (JURNAL KESEHATAN KARTIKA, 2024)
Background : Type II diabetes mellitus is a chronic metabolic disorder characterized by increased blood glucose (hyperglycemia). The global prevalence of diabetes in 2021 reached 10.5% or 537 million adults, with almost half unaware of their condition. IDF predicts this prevalence will increase to 643 million in 2030 and 783 million in 2045, with more than 90% of sufferers experiencing type 2 diabetes which is triggered by various factors. Additionally, approximately 541 million people have Impaired Glucose Tolerance (IGT), which increases the risk of type 2 diabetes (1–3). One non-pharmacological action that can be taken is hyperglycemia management which focuses on providing oral fluid intake of boiled bay leaf water, which contains flavonoids to reduce blood glucose levels by inhibiting glucose reabsorption in the kidneys. Objective: provides an overview of the effectiveness of giving bay leaf decoction in overcoming the problem of unstable blood glucose levels. Method : The research uses a qualitative case study with a case study research approach strategy. The researcher explains a descriptive research approach that focuses on overcoming unstable blood glucose levels by administering bay leaf boiled water in type II diabetes mellitus. The results : After being given bay leaf boiled water for 7 days, both respondents experienced a decrease in blood glucose levels. Respondent 1's current blood glucose level was 460 mg/dl to 237 mg/dl and respondent 2's current blood glucose level was 266 mg/dl to 224 mg/dl. conclusion : the administration of bay leaf infusion is effective in addressing blood glucose instability in patients with type II diabetes mellitus.